Serving the Whole Student: Addressing Nonacademic Barriers Facing Rural Community College Students. Issue 187 (5th September 2019) - Waters‐Bailey, Stacy; McGraw, Matthew S.; Barr, Jason
Abstract: This chapter offers strategies for creating support resources for students who face nonacademic barriers such as housing insecurity, food insecurity, lack of transportation and dependable childcare, and the need for mental health care and illness. These strategies should be viewed as ideas to help retain students and create lasting partnerships between rural community colleges and community organizations.